Protective Role of Postbiotic Mediators Secreted by Lactobacillus rhamnosus GG Versus Lipopolysaccharide-induced Damage in Human Colonic Smooth Muscle Cells. (November 2016) - Cicenia, Alessia; Santangelo, Floriana; Gambardella, Lucrezia; Pallotta, Lucia; Iebba, Valerio; Scirocco, Annunziata; Marignani, Massimo; Tellan, Guglielmo; Carabotti, Marilia; Corazziari, Enrico Stefano; Schippa, Serena; Severi, Carola
Abstract : Background: Some beneficial effects of probiotics may be due to secreted probiotic-derived factors, identified as "postbiotic" mediators. The aim of this study was to evaluate whether supernatants harvested from Lactobacillus rhamnosus GG (LGG) cultures (ATCC53103 strain) protect colonic human smooth muscle cells (HSMCs) from lipopolysaccharide (LPS)-induced myogenic damage. Materials and Methods: LGG was grown in de Man, Rogosa, Share medium at 37°C and samples were collected in middle and late exponential, stationary, and overnight phases. Supernatants were recovered by centrifugation, filtered, and stored at −20°C. The primary HSMCs culture was exposed for 24 hours to purified LPS of a pathogen strain of Escherichia coli (O111:B4) (1 μg/mL) with and without supernatants. Postbiotic effects were evaluated on the basis of HSMCs morphofunctional alterations and interleukin-6 (IL-6) production. Data are expressed as mean±SE ( P <0.05 significant). Results: LPS induced persistent, significant, 20.5%±0.7% cell shortening and 34.5%±2.2% decrease in acetylcholine-induced contraction of human HSMCs. These morphofunctional alterations were paralleled to a 365.65%±203.13% increase in IL-6 production. All these effects were dose-dependently reduced by LGG supernatants. Supernatants of the middle exponential phase already partially restored LPS-induced cell shortening by 57.34%±12.7% and IL-6 increase by 145.8%±4.3% but had no effect on LPS-induced inhibition of contraction. Maximal protective effects were obtained with supernatants of the late stationary phase with LPS-induced cell shortening restored by 84.1%±4.7%, inhibition of contraction by 85.5%±6.4%, and IL-6 basal production by 92.7%±1.2%. Conclusions: LGG-derived products are able to protect human SMCs from LPS-induced myogenic damage. Novel insights have been provided for the possibility that LGG-derived products could reduce the risk of progression to postinfective motor disorders.